Pengaruh Konsentrasi dan Frekuensi Pemberian Pupuk Organik Cair (POC) Terhadap Pertumbuhan dan Produksi Bawang Merah (Allium ascalonicum L.). - Moh. Khanif Nasuha; Sarjana Parman; Rini Budi Hastuti (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2015)
Shallots (Allium ascalonicum L) is a vegetable crop that has an important role in the economy of Indonesian society. This can be seen from the BPS (Central Bureau of Statistics) on onion consumption in the country in 2014 amounted to 935,000 tons. The high consumption of red onion cultivation resulted not memperhatiakan environmental factors are often farmers excessive use of inorganic fertilizers, resulting in soil becomes solid. Giving treatment Liquid Organic Fertilizer (POC) is expected to increase growth and yield of onion because the content of the complete haranya both micro and macro, and is also able to improve soil quality. The purpose of this research know the effect of the concentration, frequency and interaction of liquid organic fertilizer on the growth and production of onion (Allium ascalonicum L). The design used in this research was Randomized Complete Block Design (RCBD) factorial design with two factors, namelythe concentration of fertilizers and the frequency of fertilizer application. This study menggunakan6 treatment with a combination of concentration and frequency are K0F1 (0% 5 days), K0F2 (0% 10 days), K1F1 (25% 5 days), K1F2 (25% of 10 days), K2F1 (50% 5 days), K2F2 (50% of 10 days). Observations made during the 50 days after planting. Growth parameters measured were plant height and number of leaves, the production parameters measured were wet weight, dry weight, and the number of tubers. Data analysis using ANOVA test and further tests using test Duncan Multiple Test (DMRT) at 95% confidence level. The conclusion of this research is the concentration of liquid organic fertilizer (POC) significantly affect the growth parameters and onion production and the frequency and interaction no significant effect on growth parameters and onion production. Keywords: onion, organic fertilizer, concentration, frequency.